2021
DOI: 10.1002/solr.202100513
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Long‐Term Thermal Stability of 1D/2A Terpolymer‐Based Polymer Solar Cells Processed with Nonhalogenated Solvent

Abstract: Donor–acceptor (D–A) copolymer‐based polymer solar cells (PSCs) processed with nonhalogenated solvents exhibit relatively low power conversion efficiencies (PCE) due to undesirable morphological properties, including high aggregation and unfavorable orientation. Moreover, they show very poor long‐term stability owing to excessive molecular aggregation and unfavorable phase separation. Thus, novel p‐type polymers are required for high‐efficiency and long‐lived PSCs that can be processed in ecofriendly nonhaloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Absorption peaks from 500 to 700 nm can be attributed to intermolecular charge transfer (ICT) between donor and acceptor units. [30][31][32][33][34] The solution and film absorption spectra of rr-PfBT2f4T-2OD and rr-PfBT2f4T-2DT showed similar UV-vis profiles with strong vibronic shoulder peaks. Moreover, both polymers exhibited almost identical maximum absorption peaks in solution and film states, indicating that pre-aggregation occurs in solution state.…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 90%
“…Absorption peaks from 500 to 700 nm can be attributed to intermolecular charge transfer (ICT) between donor and acceptor units. [30][31][32][33][34] The solution and film absorption spectra of rr-PfBT2f4T-2OD and rr-PfBT2f4T-2DT showed similar UV-vis profiles with strong vibronic shoulder peaks. Moreover, both polymers exhibited almost identical maximum absorption peaks in solution and film states, indicating that pre-aggregation occurs in solution state.…”
Section: Optical and Electrochemical Propertiesmentioning
confidence: 90%
“…[21,27,33,34] Additionally, molecular dipole interaction was also proved effective to influence the intermolecular interaction of the terpolymers. [35] This is because the BDD unit possesses a rather low dipole moment for its symmetric aromatic structure. Thus, choosing an A 2 group with suitable dipole moment to offset the effect of entropy increment shall be an elegant method to obtain a desired morphology.…”
Section: Introductionmentioning
confidence: 99%
“…However, these solvents are detrimental to human health and the environment, and are not adaptable for industrial production due to their toxic nature and high volatility. [ 43–48 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, these solvents are detrimental to human health and the environment, and are not adaptable for industrial production due to their toxic nature and high volatility. [43][44][45][46][47][48] Therefore, efforts have been made to seek photovoltaic material systems which are suitable for fabricating high-efficiency PSCs with non-halogenated solvents. Huang et al reported a new non-fullerene acceptor DTY6 by employing the long branched alkyl chains (2-decyltetradecyl, 2-DT) to replace the 2-ethylhexy on dithie-nothiophen[3.2-b]pyrrolobenzothiadiazole (TPBT) central unit of Y6.…”
mentioning
confidence: 99%